Health Outcomes Following Traumatic Brain Injury: An Umbrella Review - Jason M. Toliao; Junhyuk Lee; Hans Oh; San Lee; Lucas Conner; Stefan Blüml; Peter A. Chiarelli; Pradip P. Chaudhari (Neuropsychology Review, 2026)
An increasing number of systematic reviews and meta-analyses examine health outcomes from traumatic brain injury (TBI). This umbrella review examines the association of TBI with comorbid health outcomes and evaluates the methodological rigor of existing literature. This protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO; Registration No. CRD42024581341). EMBASE, PubMed, MEDLINE, and the Cochrane Library were searched from database inception to November 26, 2025. Two reviewers screened abstracts and full texts using predefined criteria. Meta-analyses of observational studies were included if they assessed health outcomes following TBI and reported effect sizes were convertible to pooled equivalent odds ratios (eOR). PRISMA (Preferred Reporting Items of Systematic Reviews and Meta-Analyses) guidelines were utilized for study formatting. We applied AMSTAR2 (A Measurement Tool to Assess Systematic Reviews 2) criteria to assess the quality of included studies. Health outcomes described in each meta-analysis were reanalyzed and presented through eOR using a random-effects model. 41 meta-analyses were included, covering 671 original studies and 53 comorbid health outcomes, in a cohort comprising 83 million participants across 40 countries. Our findings suggest that traumatic brain injury, acquired at any age, may be associated with impairments across neurological, somnological, cognitive, mental health, and behavioral domains. Despite these associations, 78% of the included studies were themselves classified as having “critically low” methodological quality by AMSTAR2 criteria, which limited the ability to provide causal conclusions. These findings may help inform care guidelines following TBI. Improved research frameworks are important to better understand the lasting effects of TBI.